Explicating transcendental factors for viable digital business: Towards an explanatory model for digital start-up emergence - Emmanuel Okoro Ajah (Digital Business)
Digital start-ups leverage the power of large datasets, cloud computing, and digital technology-driven platforms to maintain a competitive edge in the entrepreneurial landscape. As a result, digital technology is a crucial tool for creating successful digital businesses. However, our knowledge of the causal interplay in digital start-up development remains limited as current literature contains few studies that focus on conceptualising and theorising the emergence of digital start-ups. Some scholars emphasise the need for new empirical research to theoretically deepen our understanding of the factors contributing to digital start-up emergence. In response, this study adopts liminality theory, enactment theory, and technology affordance theory to explain the underlying factors that drive the emergence of digital start-ups. The researcher uses a critical realist single case study methodology to explore various narratives of digital start-up founders within Nigeria's digital start-up ecosystem. The findings of this study identify the underlying mechanisms activated by digital platform boundary resources and the surrounding environmental structures and conditions. These mechanisms are integral to the events that lead to the formation of a digital start-up. The study advances the literature on digital business by developing a mechanisms-based theoretical model that outlines structures, enabling conditions, and generative mechanisms as transcendental factors. Ultimately, this study offers a detailed account of how digital platforms can facilitate digital business development. Notably, the mechanisms-based model is unique in its adaptability to different environmental circumstances and allows for flexible interpretation. This quality provides a foundation for empirical validation across various contexts, ensuring analytical generalisation.